Role of Curing Agents in the Preservation of Shelf-stable Canned Meat Products - Duncan, Charles L. (1968)
Experiments were conducted to gain a better understanding of the mechanism by which sodium chloride, sodium nitrate, and sodium nitrite supplement the action of heat in preserving canned cured meat products. Heated spores of putrefactive anaerobe 3679h were less tolerant of all three curing agents in the outgrowth medium than were unheated spores. When the curing agents were added to the heating menstruum, but not to the outgrowth medium, sodium chloride and sodium nitrate tended to protect the spores against heat injury, but sodium nitrite did not. When the spores were both heated and cultured in the presence of the curing agents: (i) nitrate and salt increased the apparent heat resistance at low concentrations (0.5 to 1%) but decreased it at concentrations of 2 to 4%; (ii) nitrite was markedly inhibitory, especially at pH 6.0. At the normal pH of canned luncheon meats (approximately 6.0), nitrite appears to be the chief preservative agent against spoilage by putrefactive anaerobes.